(untitled) (Eurasian Journal of Media and Communications, 2024)
This article focuses on the unique work of Rahmatjon Tursunov, a child of the Khorezm people, a Davidic voice, an artist, composer and musician who served in Uzbekistan. Rahmatjon Tursunov is one of the famous khafiz of his time, successor of Komiljon Otaniyozov’s unique musical creation and promoter of Khorezm art. Although there is not a lot of information about the singer, we tried to highlight their creative works as much as possible. We have analyzed some of the samples of Mermanshul’s creations and included the author’s poetic texts. It can be observed that they are not only musicians, composers, and status scholars, but also possess sufficient knowledge in literature and poetry.